Swarm intelligence and deep evolution : evolutionary approach to artificial intelligence - Iba, Hitoshi ([Place of publication not identified] : CRC Press, 2022)
"Our book covers recent developments in swarm intelligence, deep learning, and evolutionary computation for the sake of practical AI application so that a larger audience of researchers and practitioners can be expected from the computer science. It also keeps the mathematics to a minimum; as much as possible, mathematical formulas and programs were generally not used"--
1. AI: Past and Present 2. Evolutionary Theories for AI 3. Evolutionary Computation 4. Swarm Intelligence 5. Deep Learning and Evolution 6. Deep Swarms and Evolution 7. Emergence of Intelligence
OCLC-licensed vendor bibliographic record.
Keywords: COMPUTERS / Programming / Systems Analysis & Design; SCIENCE / Life Sciences / Biology / General; SCIENCE / Life Sciences / General; Swarm intelligence; Evolutionary computation